THE EXISTENCE AND EFFECTIVENESS OF THE LAW ON THE APPLICABILITY OF THE CONSTITUTIONAL RIGHTS OF CITIZENS-NATURALIZATION IN ELECTIONS IN INDONESIA - Rifandhana, Raditya Feda; Budiono, Indro; Ningtias, Ayu Dian; Nurita, Riski Febria; Wahyono, Bambang Angkoso (Jurnal Independent, 2022)
Abstract Indonesia is a country based on the Constitution of the Unitary State of the Republic of Indonesia of 1945, so that the basis of the country, has a basis on which it regulates human rights, human rights are not only the rights of Indonesian citizens, but the rights of foreign citizens through naturalization, both citizen statuses have the same rights in elections, and in this writing using juridical research, So that the research is based on laws and regulations, as well as a research approach with legal theory.